PELATIHAN MUSYAWARAH GURU MATA PELAJARAN (MGMP) DAN INSENTIF TERHADAP KINERJA GURU - Maghfira, Intan; Mustar, Saidil; Ifnaldi, Ifnaldi; Faishol, Riza (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
The purpose of this study was to determine the effects of subject teacher consultation training (MGMP) and incentives on teacher performance in private MTS in Curup District. This was a descriptive quantitative study. The population engaged all private MTs teachers in Curup District totaling 95 people. This study deployed a purposive sampling technique, so that 50 people were obtained as the samples according to the criteria. The instrument used was a questionnaire and documentation. The analysis employed descriptive percentage analysis method and multiple linear regression. The results of the regression analysis at the 5% confidence level showed that MGMP training and incentives contributed 71.89% to the performance of teachers in private MTS in Curup District, and the partial contribution from MGMP training was 53.3% and incentive was 62.8%. This study concluded that there were significant effects of MGMP training and incentives on teacher performance in a high category. This showed that the overall performance of teachers in private MTS in Curup District was influenced by the level of MGMP training and the amount of incentives.